PENERAPAN POSITIVE PARENTING DALAM PEMBIASAAN POLA HIDUP BERSIH DAN SEHAT KEPADA ANAK USIA DINI - Wiranata, I Gusti Lanang Agung (PRATAMA WIDYA : JURNAL PENDIDIKAN ANAK USIA DINI, 2020)
Early childhood education or PAUD is not only about educating, it also includes parenting and protecting children, as well as supporting children’s healthcare. Healthcare is one of the main parts because it affects child’s development in general. Taking care of children’s health is the direct responsibility of the parents, together with the teachers at school and should be also supported by the Government. Parents, as the closest ones to their children have to take care of them and introduce them the healthy lifestyle. This will be the basis of the children’s self-protection in the future. In getting the child to get used to the clean and healthy lifestyle, parents should also consider the characteristics and the development of their children. In parenting, parents need to implement positive parenting so that the children will feel more comfortable and will respond the stimulation well. Positive parenting is a type of parenting method that is based on affection, respect and good relationship between the parents and their children. Implementation of parenting method that is based on appreciation and understanding to the children will minimize child rejection.